Factors affecting the choice of equity-based mode by Foreign firms entering Kazakhstan - Abuova, Aigerim; Ra, Wonchan (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
Choice of modes is a critical decision that firms conducting equity-based foreign direct investment must make since it has a significant effect on performance. Entry mode choice has been a major topic in international business research up to now. As the largest country in size in Central Asia and a large economic potential, Kazakhstan became one of the main destinations for foreign direct investment in this area while transitioning to a market-based economy after gaining independence from the Soviet Union in 1991. This paper investigates the main firm- and country-specific factors that affect the choice of equity-based entry modes of foreign investors entering Kazakhstan between a joint venture (JV) and a wholly-owned subsidiary (WOS). We establish hypotheses regarding the effects of such factors on the mode choice and empirically test the hypotheses with secondary data on foreign companies’ entry in Kazakhstan, using binomial logit regression analysis.